Avian Pathogenic Escherichia coli: An Overview of Infection Biology, Antimicrobial Resistance and Vaccination - Amyleigh Watts; Paul Wigley (Antibiotics)
Avian Pathogenic Escherichia coli (APEC) is an extraintestinal pathotype of E. coli that leads to a range of clinical manifestations, including respiratory, systemic and reproductive infections of chickens in both egg and meat production. Unlike most E. coli pathotypes, APEC is not defined by specific virulence genes but rather is a collection of several distinct genotypes that can act as both primary and secondary pathogens leading to colibacillosis. Recent measures to reduce antimicrobials both as growth promoters and as flock-level therapeutics are considered to have led to increased numbers of animals affected. Nevertheless, antimicrobial resistance is a considerable problem in APEC, with resistance to third and fourth-generation cephalosporins via extended-spectrum beta-lactamases (ESBLs), fluoroquinolones and colistin seen as a particular concern. The need to control APEC without antimicrobial use at the flock level has seen an increased focus on vaccination. Currently, a few commercial vaccines are already available, and a range of approaches are being applied to develop new vaccines, and other controls, such as bacteriophage or probiotics, are attracting interest. The lack of a single defined APEC genotype presents challenges to these approaches.